The Effectiveness of Employee Performance in Improving Services at the Religious Affairs Office (KUA) of Cigeulis District, Pandeglang Regency - Ombi Romli; Ujang Saidi (Business and Investment Review, 2023)
This study aims to analyze the effectiveness of employee performance in improving public services at the Office of Religious Affairs (KUA) of Cigeulis District, Pandeglang Regency. Effectiveness is measured by the extent to which employees carry out their duties and responsibilities according to public service standards. The research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. Seven informants were selected purposively from community members and KUA officials. Data were analyzed using qualitative analysis and triangulation techniques to ensure validity. The findings indicate that the performance of KUA employees in Cigeulis District is generally effective in providing services to the community. Employees have implemented their duties according to established procedures and have prioritized community satisfaction. However, several challenges remain, including limited human resources, inadequate facilities, and uneven workloads. The study concludes that enhancing employee performance effectiveness requires continuous training, improved infrastructure, and better managerial systems to optimize public service delivery at the KUA.